Ammonium acetate and ethylenediamine-assisted synthesis of anatase nanocrystals with 0 1 0 facets and enhanced photocatalytic activity. Issue 2 (June 2015) - Wang, Penghua; Lei, Juying; Xing, Mingyang; Wang, Lingzhi; Liu, Yongdi; Zhang, Jinlong
Highlights: Rhombic anatase nanocrystals were synthesized by a facile green solvothermal approach. Ammonium acetate and ethylenediamine act as structure directing agents. The nanocrystals possess large percentage of 0 1 0 facets up to 73%. The nanocrystals have small average particle size and large surface area. The nanocrystals have superior photocatalytic activity to commercial anatase and P25. Abstract: This work reports a facile green solvothermal approach to synthesize rhombic anatase TiO2 nanocrystals with small particle size of 50 nm and large percentage of 0 1 0 facets up to 73%. Tetrabutyl titanate (TBOT) is used as the titanium precursor while ethanol as the reaction solvent. The key strategy of this approach is to utilize ammonium acetate (AMAT) and ethylenediamine (EDA) in the non-aqueous system, where AMAT promotes the hydrolysis of TBOT and EDA serves as the capping agent. AMAT and EDA act synergistically to achieve a controlled growth of crystal structure of the anatase TiO2 nanocrystals with exposed 0 1 0 facets. The mechanism for the nanocrystal growth was proposed based on experimental evidence. And the photocatalytic activities of the resultant nanocrystals were evaluated by degradation of methyl orange. This nanocrystal exhibits a superior photocatalytic activity in reference to commercial anatase TiO2 and P25, owing to the large percentage of exposed 0 1 0 facets along with large surface area resulting from the small particle size.